Digital Promotion Strategies through Instagram to Drive Consumer Purchase Intention in MSMEs - Bunga Shafira; Komarun Zaman; Nur Aini Anisa (Penerbit Goodwood, 2026)
Purpose: This study aims to explore how promotion strategies through Instagram can increase consumer purchase intention towards micro, small, and medium enterprises (MSMEs) in Jakarta. Methodology/approach: This research employs a descriptive qualitative approach. Data were collected through in-depth interviews with eight MSME owners from the food, fashion, and interior design sectors, along with four active Instagram consumers. The data collection techniques included interviews, Instagram account observation, and digital documentation. Data were analyzed using thematic analysis. Results/findings: The findings indicate that the most effective strategies involve collaboration with micro-influencers, the use of authentic visual content, momentum-based promotion through Instagram Ads, and active consumer interaction via Instagram features such as Stories and Reels. These results align with the Customer Path 5A theory, AIDA model, Electronic Word-of-Mouth, and Brand Engagement concepts, highlighting that strategic, relatable, and timely engagement can significantly enhance brand visibility and consumer loyalty in the digital marketplace. Conclusion: Instagram is an effective digital promotion channel for MSMEs in Jakarta when strategies combine authentic high-quality visuals, responsive two-way communication, and credible social validation through micro-influencers and customer testimonials. These integrated approaches strengthen engagement and trust, ultimately increasing consumer purchase intention and supporting sustainable digital marketing performance. Limitations: This study is limited to MSMEs in Jakarta with a small number of respondents, which may not represent all sectors or regions. Contribution: This research provides practical contributions for MSME actors to optimize digital promotion strategies through Instagram and enriches the literature on social media marketing in the MSME context.